Improving creative thinking skills and scientific attitude through inquiry-based learning in basic biology lecture toward student of biology education - Sandika, Bayu; Fitrihidajati, Herlina (Jurnal Pendidikan Biologi Indonesia, 2018)
Creative thinking skill and scientific attitude are one of 21st century skills which have to be taught to students in the learning process. The pre-study result indicated that only a few of learning process is provided by scientific activities which can assist students to comprehend the concepts easier and improve the studentsâ creative thinking skill and scientific attitude. Inquiry-based learning can be an alternative to provide an active and authentic scientific learning process. This study aims at improving creative thinking skill and scientific attitude through inquiry-based learning in basic biology lecture toward students of biology education. This study is included in a descriptive quantitative research. The research focused on the topic of cell transport which was taught toward 25 students of Biology 2 class from 2017 academic year of Biology Education Department. The learning process was conducted in two meetings on November 2017. The enhancement of studentsâ creative thinking skill was determined by one group pre-test and post-test research design using test instrument meanwhile the scientific attitude focused on curiosity and objectivity were observed using non-test instrument. Research result showed that studentsâ creative thinking skill enhanced highly and studentsâ scientific attitude improved excellently through inquiry-based learning in basic biology lecture.